Penerapan Metode Pembelajaran Project Based Learning Menurut Kurikulum Prototipe untuk Pembelajaran Matematika yang Bermakna - Windi Kristiato Yohanis Bell; Kurnia Putri Sepdikasari Dirgantoro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Most students think that the hardest subject to understand is math. It happened when the student did not get the meaning of doing math. It was made worse by the covid situation, students more and did not get any value. Even though the government had provided curriculum and lesson method options to be held in class, still it can be maximized to create meaningful math lessons. Therefore, this research focuses on the application of the Project-Based Learning (PjBL) method based on a prototype curriculum to make math lessons more meaningful. The research method that will be used is descriptive qualitative. Students must get meaningful math lessons to find the greatness of God by doing math in their daily lives. Finally, students also glorify God. The research result is, PjBL based on the prototype curriculum method can help make learning mathematics more meaningful. The writer suggests for schools, hold training on using PjBL based on the curriculum prototype method, for teachers to apply this method in abstract topics, and for the next researcher to research the application of the PjBL method based on another curriculum.